Evaluation du potentiel de réactivité des bétons vis-à-vis de la formation différée de l'ettringite - EL BECHIR Faiza (My University, 2012)
Delayed ettringite formation (DEF) is a pathology of cementitious materials that has been widely studied these past years. If ettringite forms only partially during the beginning of cement hydration (its solubility increases with temperature and alkali content), the late crystallization of the remaining ettringite in a hardened material stored in wet conditions, without any external sulphate supply, can be associated with a global swelling of the material. DEF can be identified if this swelling generates damage at the level of the material or the structure. This phenomenon can cause concrete specimens to expand by about 1 % in unrestrained conditions of expansion, leading to important damage in field structures as cracks affecting the whole concrete. Nowadays there are only few recognized cases because this pathology requires the concomitance of several conditions. These cases have been identified in steam-cured precast concretes and in non-heat-treated massive concrete members. In this second case, the heat associated with cement hydration can generate by itself high temperature in the heart of the concrete member. The scientific literature is rich in publications and experimental results, especially on samples of paste (cement and water) or mortar (cement, sand and water), but relatively little effect on the concrete itself. However, the concrete is at the heart of the problem. The reason why focus is on the paste and motor is due to the excessively long period of testing concrete. At the results of the studies are often contradictory and contested. One of the objectives of the Memorial was to provide a better understanding of the development of this chemical reaction. The mechanism of swelling that involves many parameters relatively well known, namely a temperature exceeding 60° C, the composition of concrete and environment conservation of high humidity. For we have initiated research, physico-chemical studies were performed on four samples concrete from of concrete structures of Algiers and more than 20 years of age. In this Memorial, we present the main results and interpretations of the various analyzes carried out to know the TG-DTA, XRD and FX. Finally, we propose recommendations for prevention of disorders engendered by this Pathology and means of redress for the sustainability of concrete structures
Keywords: Delayed ettringite formation (DEF); Concrete; Mortar; Pathology; Warm-up; Humidity; Expansions; Sulfates; Alkaline